Poverty Alleviation as an Economic Problem. (10th April 2018) - Martin, Adam; Petersen, Matias
Abstract: Economists distinguish between technological problems, in which variable means confront a given end, and economic problems, in which given means are allocated across competing ends. James Buchanan and F. A. Hayek each offer constructive criticisms of the standard definition of an economic problem, arguing that economists too easily slide into mechanistic and teleological thinking. Building on these accounts, we argue that there are three key dimensions to the economic problem: exchange, coordination and governance. We then make a case that poverty alleviation is more like an economic problem than a technological one, an economic problem with a small 'e'. We survey empirical evidence from economics, anthropology and sociology indicating that poverty is not a simple lack of objectively identifiable resources but rather a multidimensional and socially embedded phenomenon. Understanding what poverty alleviation would even look like requires thinking through problems of exchange, coordination and governance.